Identification of Transcribing Errors in Prescriptions for Type 2 Diabetes Mellitus Patients at Clinic X, Jember - Haris Agung; Shinta Mayasari; Fendy Prasetyawan (Indonesian Pharmacopeia Journal, 2025)
Abstract Background: Clinical Pharmacy Services play an important role in health services in hospitals. Pharmaceutical service standards are direct and responsible services to patients related to pharmaceutical preparations with the aim of achieving definite results to improve the quality of life of patients. Medication error (ME) is an incident that causes or has an impact on inappropriate drug services or endangers patients when the drug is under the control of health workers or patients. Transcribing Error (TE) is an error in reading a prescription before entering the dispensing stage. TE includes changes to the drug name, drug formulation, route, dose, dosage regimen to prescription orders. According to the East Java Health Service in 2021, Diabetes Mellitus (DM) sufferers in East Java were 2.6 of the population aged 15 years and over. Health services for diabetes mellitus sufferers at first-level health facilities (FKTP) in 38 districts/cities throughout East Java reached 867,257 cases (93.3% of the estimated DM sufferers. Based on dataBasic Health Research, 2021cases of diabetes mellitus in Jember amounted to 1.4%. This study aims toIdentifying transcription errors in prescriptions for type 2 DM patients at clinic x, Jember district. This research uses research descriptive using observation method The data source taken from this study is data from outpatient prescriptions for type 2 Diabetes Mellitus for the period January - December 2022-2024 at clinic x Jember district. The population of this study was 37 medical prescriptions for outpatients with type 2 DM for the period January - December 2022-2024 at clinic x Jember. The sample in this study was prescription data for patients diagnosed with type 2 DM who met the inclusion and exclusion criteria with a total of 37 samples by total sampling. The results of this study were obtained. Data from the identification of transcription errors still contained errors. From the total sample taken, 37 prescriptions, the results of the identification of transcription errors still contained errors including no medical record number (89.2%) no patient age (45.9%) no dosage form (43.2%). While the parameters of patient name, drug name, dosage, duration of administration, route of administration, date of prescription request have been complete, there are no errors.From the discussion above, it can be concluded that the results of transcription error identification still contain errors. Keywords:Medication error, transcribing error, DM type 2